Implementación de un sistema de monitoreo, registro y control de temperatura para cultivos de semillas de un invernadero del campus Salache. - Nata Rivera, Edisson David (2019)
Implementation of a system for monitoring, recording and temperature control for seed crops of a greenhouse of the campus Salache developed in order to establish an optimal range of the physical temperature variable between 18°c and 30°c, being are the right conditions for the proper development of seed crops. The automation system is carried out by means of an electrical and electronic system controlling the variant of interest allowing monitoring quickly and accurately according to the behavior that may present during data collection from the sensor at the top of the greenhouse, allowing the user to easily manage the system and obtaining real measures stored in the data base. The system consists of a k-type thermocouple sensor and two motors with a power of 0.80 HP located at the end of each end of the greenhouse, these allow to obtain a proper tempering flow by considerably reducing the high temperatures which may be harmful during the germination process, according to the source temperature it is within the 41°c therefore the activation of the side windows will be carried out from a temperature of 18°c decreasing significantly a 6% ,if the temperature does not drop the air extractor activation will be performed during a temperature of 31°c,approximately decreasing by 11%, simultaneously if the temperature does not decrease at this point, activation of the misting process is carried out during a temperature of 35°c, decreasing to the preset initial temperature ranges, With the implementation of the system is intended to provide correct development of the cultivation of andean grain seeds.